EFFECTS OF PLANT PREPARATIONS OF PURE SAPONINS AND METHOXYFLAVONOIDS ON THE EXPRESSION OF IMMUNE RESPONSE GENES - Turmagambetova , A.S.; Bogoyavlenskyi, A.P.; Alexyuk , P.G.; Alexyuk, M.S.; Omirtaeva , E.S.; Sokolova , N.S.; Zaitseva , I.A.; Berezin , V.E. (Eurasian Journal of Applied Biotechnology, 2019)
Studies on the immunostimulating properties of saponins and methoxyflavonoids obtained from plants provides a theoretical basis for development of new immunopotentiators, thereby increasing effectiveness of immunotherapy and prophylaxis of viral infections. Expression of major genes of the immune response were significantly up-regulated upon introduction of plant-based immunostimulators into the body. These compounds were a mixture of purified saponin betulin isolated from plants of Betula sp. (Betula pendula) and purified methoxyflavonoids of plants of Polygonum sp. (Polygonum persicaria) and Cytrus sp. (Cytrus sinensis). The strength and specificity of the body’s immune response can be adjusted by changing the structure of the methoxyflavonoid in the complex immunostimulator, which makes it possible to stimulate targeted immunostimulators that act on certain parts of the immune system.